The Palgrave Handbook of Audiovisual Translation and Media Accessibility 2020
DOI: 10.1007/978-3-030-42105-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Reception Studies and Audiovisual Translation

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…To investigate the reception of AVT, it is necessary to explore how audience reception occurs during authentic viewing experiences, with viewers consuming translated audiovisual materials (Tuominen 2018). and Di Giovanni (2020) suggest the use of mixed methods in research focusing on the reception of AVT from an empirical perspective. In this regard, this pilot study adopted a multi-method approach (Tuominen 2018) based on the user-centered translation model (Suojanen et al 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the reception of AVT, it is necessary to explore how audience reception occurs during authentic viewing experiences, with viewers consuming translated audiovisual materials (Tuominen 2018). and Di Giovanni (2020) suggest the use of mixed methods in research focusing on the reception of AVT from an empirical perspective. In this regard, this pilot study adopted a multi-method approach (Tuominen 2018) based on the user-centered translation model (Suojanen et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, reception studies emerge as an essential research field seeking to unravel the complexities of how these choices influence the audience's comprehension, emotional engagement, enjoyment, and overall viewing experience (Di Giovanni and Gambier 2018). Reception studies in AVT stand at the forefront of understanding how audiences engage with and interpret audiovisual content in its various translated forms (Gambier 2018;Di Giovanni 2020). This field acknowledges that the impact and effectiveness of audiovisual translation extend beyond the technical aspects of language transfer, delving into the intricate dynamics of how viewers from diverse linguistic and cultural backgrounds receive, perceive, and interact with audiovisual translations (Di Giovanni and Gambier 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By the same token, dubbing research currently investigates the translators' role, their choices, what mediates such choices, the translation and adaptation of the audiovisual product, and the audience's active role in today's digitized and multimodal world (Chaume 2020). The last turn centered on AVT experimental research, where researchers test the audience perception of major dubbing features, like lip-synchrony and kinetic synchrony (Giovanni 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is no lack of reviews in the AVT literature, with two most recent ones being Orrego-Carmona (2019) and Di Giovanni (2020). These reviews take stock of what AVT research has achieved and offer suggestions to move the field forward.…”
Section: Making a Case For A Systematic Reviewmentioning
confidence: 99%
“…Our review also found that about one third of the experiments relied on one research instrument. As the production and reception of AVT contents are complex in nature, researchers are suggested to use multiple research instruments to collect data and triangulate data interpretation (Di Giovanni, 2020;Orero et al 2018).…”
Section: Research Designsmentioning
confidence: 99%